Combined analyses of translatome and transcriptome in Arabidopsis reveal new players responding to magnesium deficiency. Issue 12 (2nd November 2021) - Li, Yaxin; Li, Qianqian; Beuchat, Gabriel; Zeng, Houqing; Zhang, Cankui; Chen, Li‐Qing
Abstract: Translational control of gene expression, including recruitment of ribosomes to messenger RNA (mRNA), is particularly important during the response to stress. Purification of ribosome‐associated mRNAs using translating ribosome affinity purification (TRAP) followed by RNA‐sequencing facilitates the study of mRNAs undergoing active transcription and better proxies the translatome, or protein response, to stimuli. To identify plant responses to Magnesium (Mg) deficiency at the translational level, we combined transcriptome and translatome analyses. Excitingly, we found 26 previously unreported Mg‐responsive genes that were only regulated at the translational level and not the transcriptional level, during the early response to Mg deficiency. In addition, mutants of the transcription factor ELONGATED HYPOCOTYL 5 (HY5), the H + /CATION EXCHANGER 1 and 3 (CAX1 and CAX3), and UBIQUITIN 11 (UBQ11) exhibited early chlorosis phenotype under Mg deficiency, supporting their functional involvement in ion homeostasis. Overall, our study strongly supports that TRAP‐seq combined with RNA‐seq followed by phenotype screening could facilitate the identification of novel players during stress responses. Abstract : Translatome and transcriptome profiling identified 26 ribosome‐associated RNAs regulated by magnesium deficiency. Moreover, mutant analysis showed that mutants of four of these genes, ELONGATED HYPOCOTYL 5, two H + /cation exchanger genes ( CAX1 and CAX3 ), and UBIQUITIN11, exhibited early chlorosis, supporting their involvement in responding to magnesium deficiency.